Re-using Criterion plastic precast gel cassettes for SDS-polyacrylamide electrophoresis. - Sattlegger E; Anderson R (https://protocolexchange.researchsquare.com/article/pex-1302/v1, 2021)
Precast gels are made with plastic cassettes which usually are discarded after use. Here we describe how Criterion plastic gel cassettes can be re-used for making SDS-PAGE gels in-house.